MOLECULAR Characterization of Salmonella enterica SEROVARS in Broiler Chickens at Kafr El-Sheikh Governorate, Egypt - Amgad A. Moawad; Ahmed M. Ammar; Nagwa S. Rabie; Mohamed R. Sherief; Ibrahim E. Eldesoukey (Journal of Animal and Plant Sciences, 2022)
Salmonella spp. are one of the most frequently reported foodborne pathogens worldwide. The present study investigated the virulence genotypes and antimicrobial sensitivity of Salmonella spp. isolated from broiler chickens in Kafr El-Sheikh governorate, Egypt. A total of 180 samples [liver (n=70), spleen (n=70) and caecum (n=40)] collected from 50 different broiler chicken flocks were used to isolate Salmonellae. All suspected samples were examined through a series of conventional bacteriological, biochemical, and serological techniques for isolation and identification of Salmonella spp. All isolates were tested for susceptibility to 16 antimicrobials. Virulence factors were determined using the polymerase chain reaction assays targeting the invA, pefA, avrA, sopB and spvC. The overall isolation percentage of Salmonella was 6.1%. Eleven Salmonella isolates belonging to four different serovars were recovered. S. Belgdam was the most predominant species (7/11, 63.6%), followed by S. Typhimurium (2/11, 18.2%), and S. Virchow and Salmonella enterica subsp. Salamae (S. Salamae) (1/11, 9.1% each). All the isolates were positive for all tested genes except S. Salamae, which harbored neither the sopB nor avrA genes. All isolates exhibited resistance to almost all antimicrobials used. The finding of the present study show high positivity of virulence genes as well as multidrug resistance of all serotypes suggesting pathogenic Salmonella strains.
Keywords: Salmonella; Chicken; cPCR; Virulence genes; Antimicrobials